Achieving excellent energy storage density of Pb0.97La0.02(ZrxSn0.05Ti0.95-x)O3 ceramics by the B-site modification. Issue 1 (January 2021) - Zhang, Yujing; Liu, Pin; Kandula, Kumara Raja; Li, Wenru; Meng, Shen; Qin, Yanfeng; Zhang, Haibo; Zhang, Guangzu
Abstract: The applications of antiferroelectric (AFE) materials in miniaturized and integrated electronic devices are limited by their low energy density. To address the above issue, the antiferroelectricity of the reinforced material was designed to improve its AFE-ferroelectric (FE) phase transition under electric fields. In this present study, the composition of Zr 4+ (0.72 Å) and Ti 4+ (0.605 Å) at B-site of Pb0.97 La0.02 (Zr x Sn0.05 Ti0.95- x )O3 ceramics with orthogonal reflections are synthesized via the tape-casting method. These ceramics are modified to enhance their antiferroelectricity by reducing their tolerance factor. A recoverable energy storage density W rec 12.1 J/cm 3 was obtained for x = 0.93 under 376 kV/cm, which is superior value than reported until now in lead-based energy storage systems. Moreover, the discharge energy density can reach 10.23 J/cm 3, and 90 % of which can be released within 5.66 μs. This work provides a new window and potential materials for further industrialization of pulse power capacitors.